Wild-type Transthyretin Amyloid Myopathy With an Inclusion Body Myositis Phenotype. Issue 1 (September 2020) - Huser, Sara; Loavenbruck, Adam; Manousakis, Georgios
Abstract : Abstract: Senile systemic amyloidosis (SSA), or wild-type transthyretin (wtATTR) amyloidosis, is associated most commonly with cardiomyopathy and carpal tunnel syndrome. SSA-associated skeletal myopathy is rare. We describe the case of a patient with SSA who exhibited asymmetric quadriceps and finger flexor weakness, a phenotype usually seen in inclusion body myositis.